Murder on Mustang Beach [large type] - Bessette, Alicia (Bessette, Alicia. Outer Banks bookshop mystery, 2023)
"Cattail Island in the Outer Banks is a popular destination for honeymooners and nature lovers alike. So it is a huge blow when the murder of a newlywed grinds the pre-summer season to a screeching halt. Bookseller Callie Padget launches her own investigation, after mysterious customer Geri-Lynn Humfeld, caretaker of the island's protected wild horses, brings in an irresistible piece of information. Determined to restore order and safety to her beloved hometown, Callie searches for answers--even as those answers cast suspicion on her soon-to-be boyfriend, Toby Dodge, whose martial arts studio was the scene of the crime. As she digs deeper, Toby becomes the police's prime suspect. The truth raises troubling questions and sends her scouring the bookshop's shelves for guidance. Meanwhile, a well-loved member of the mustang herd--a pregnant mare whose anticipated foal is a symbol of summery hope for locals and visitors alike--may be facing dire circumstances. With help from Geri-Lynn, Callie unearths startling secrets surrounding not only the compromised mare, but the murdered newlywed, too. And when another body shows up, this time on isolated Mustang Beach, she must race against time to stop a killer from claiming any more innocent lives"--